Teknik bibliokonseling sebagai treatment untuk meningkatkan empati siswa - Rizki Ariska; Khairul Bariyyah; Eva Kartika Wulan Sari (Psychocentrum Review, 2019)
This research aims to: 1) to know level of student empathy before the application of bibliokonseling techniques, 2) to know level of student empathy after the application of bibliokonseling techniques and 3) to know effectiveness from bibliocounseling techniques. This research using the experimental method with design of one group pretest-posttest designs type pre-experimental research, research samples amounted to 5 students who were netted using purposive sampling techniques. This research instrument is an empathy scale. Data analysis using Wilcoxon non parametric test statistics. The results of research show that 1) level of student empathy before using bibliokonseling techniques in the low category, 2) after bibliokonseling techniques level of student empathy become a high category, 3) bibliokonseling techniques effective to increase student empathy. Based on the results of this research then it is recommended: 1) for counselors in using bibliocounseling techniques as an alternative for student to have low empathy, counselor can use bibliokonseling ingredients are in accordance with student problem, 2) for other researchers can develop a bibliokonseling techniques guide book.